Layer-by-layer assembled cell instructive nanocoatings containing platelet lysate - Oliveira, Sara M. (2015)
Great efforts have been made to introduce growth factors (GFs) onto 2D/3D constructs in order to control cell behavior. Platelet Lysate (PL) presents itself as a cost-effective source of multiple GFs and other proteins. The instruction given by a construct-PL combination will depend on how its instructive cues are presented to the cells. The content, stability and conformation of the GFs affect their instruction. Strategies for a controlled incorporation of PL are needed. Herein, PL was incorporated into nanocoatings by layer-by-layer assembling with polysaccharides presenting different sulfation degrees (SD) and charges. Heparin and several marine polysaccharides were tested to evaluate their PL and GF incorporation capability. The consequent effects of those multilayers on human adipose derived stem cells (hASCs) were assessed in short-term cultures. Both nature of the polysaccharide and SD were important properties that influenced the adsorption of PL, vascular endothelial growth factor (VEGF), fibroblast growth factor b (FGFb) and platelet derived growth factor (PDGF). The sulfated polysaccharides-PL multilayers showed to be efficient in the promotion of morphological changes, serum-free adhesion and proliferation of high passage hASCs (P>5). These biomimetic multilayers promise to be versatile platforms to fabricate instructive devices allowing a tunable incorporation of PL.